Dickens, Nicholas Nickleby and the dance of Death - Tambling, Jeremy (Routledge,Taylor & Francis Group, 2019)
Introduction: Early Dickens – From papers to novel – Mr Squeers – Benevolence and humour – Pantomime and melodrama – Of
9780367143084
Keywords: Dickens; Charles; Nicholas Nickleby; Dance of death in literature